2021
DOI: 10.3390/pathogens10111375
|View full text |Cite
|
Sign up to set email alerts
|

Fall of Community-Acquired Pneumonia in Children following COVID-19 Non-Pharmaceutical Interventions: A Time Series Analysis

Abstract: Non-pharmaceutical interventions (NPIs) were implemented to reduce the spread of coronavirus disease 2019 (COVID-19). A first national lockdown was decided in France on the 17 March 2020. These measures had an impact on other viral and non-viral infectious diseases. We aimed to assess this impact on community-acquired pneumonia (CAP) in children. We performed a quasi-experimental interrupted time series analysis. We used data from a French prospective surveillance system of six pediatric emergency departments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…It has been reported that the rhinovirus positivity rate remained stable in France after NPI implementation. 41 Other respiratory viruses are not monitored in France, 42 and their epidemiological activity could not be included in our model.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the rhinovirus positivity rate remained stable in France after NPI implementation. 41 Other respiratory viruses are not monitored in France, 42 and their epidemiological activity could not be included in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory diseases, especially pneumonia, are major causes of hospitalization and death among children younger than five years. Recently, a dramatic decrease in pediatric respiratory infections, such as pneumonia, bronchiolitis, and influenza, has been observed worldwide and deemed as the result of the interruption of person-to-person viral or bacterial transmission attributed mainly to mask-wearing, social distancing, and school closure( Cheng et al, 2020 , Rybak et al, 2021 , Sakamoto et al, 2020 , Van Brusselen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly with our data, the precautions taken, such as the use of masks and social distancing, have been reported to be effective in reducing the consumption of antibiotics in 2020: 18.2% in Italy and to 23.9% in Abruzzo [ 32 ]. Also Ryabak et al analysis demonstrates CAP reduction, especially in children [ 33 ]…”
Section: Discussionmentioning
confidence: 99%